Analisis Framing “Zero Tolerance” Pada Film Indonesia: Diversity Under Threat di Youtube DW Documentary - Fitri Rezkia; Syahrul Abidin; Rholand Muary (Mahesa Research Center, 2022)
This paper aims to find out how DW Documentary frames the meaning and perpetrators of “zero tolerance” which is considered at threat in Indonesia trough journalistic work in the form of the documentary film, Indonesia: Diversity under Threat. The problem is focused on how to frame the media in presenting the film. To approach this problem, the theoretical basis of Peter L. Berger & Thomas Luckmann is used, namely the social construction of reality which is innovated into the social construction of mass media and the theory of Pamela J. Shoemaker & Stephen D. Reese, namely the theory of the hierarchy of influence. The research approach used is a qualitative approach. The data were collected through observation techniques, namely in depth observations and analyzed through framing analysis of the Zhongdang pan dan Gerald M. Kosicki model. This study concludes that DW Documentary frames the meaning of “zero tolerance” as the biggest threat to the Indonesian state, namely religious intolerance and corruption. In terms of religious intolerance, the media through the choice of words, statements, and quotes frame the label for a populist Muslim community. In this case, the media specializes in conservative Islam, through Syariah law which is considered to discriminate against minority communities, contrary to human rights and feminism. The perpetrators of intolerance were discussed with fundamentalist and radicals with violence, injustice, and does not accept differences or called intolerance.